Issues and Challenges of Road Accidents in India: A State wise Analysis: A Comprehensive Study on Road Accidents in India (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Road traffic accidents deaths and injuries occur worldwide. In the last decade alone, India lost 1.3 million people to avertable road accident and another 5.3 million have been left disabled for life. Road traffic accident (RTA) is one of the major escapable public health problems and is on the rise which can be attributed to increase in the number of vehicles and lifestyle changes and risky attitudes. Road deaths in India are publicly evident, while road safety is professionally lacking and politically missing. The objective of the study is to help produce designs and roads that reduce the number and severity of crashes and to reduce likelihoods of accidents in India by providing an overview of the whole situation of fatal road accidents in India.